Effects of Pruning in Monterrey Pine Plantations Affected by Fusarium circinatum. - Bezos García, D.; Lomba, J. María; Martínez-Álvarez, P.; Fernández, M.; Diez, J. J. (Forest Systems, 2012)
Fusarium circinatum Nirenberg and O’Donnell (1998) is the causal agent of Pitch Canker Disease (PCD) in Pinus species, producing damage to the main trunk and lateral branches as well as causing branch dieback. The disease has been detected recently in northern Spain in Pinus spp. seedlings at nurseries and in Pinus radiata D. Don adult trees in plantations. Fusarium circinatum seems to require a wound to enter the tree, not only that as caused by insects but also that resulting from damage by humans, i.e. mechanical wounds. However, the effects of pruning on the infection process have yet to be studied. The aim of the present study was to know how the presence of mechanical damage caused by pruning affects PCD occurrence and severity in P. radiata plantations. Fifty P. radiata plots (pruned and unpruned) distributed throughout 16 sites affected by F. circinatum in the Cantabria region (northern Spain) were studied. Symptoms of PCD presence, such as dieback, oozing cankers and trunk deformation were evaluated in 25 trees per plot and related to pruning effect. A significant relationship between pruning and the number of cankers per tree was observed, concluding that wounds caused by pruning increase the chance of pathogen infection. Other trunk symptoms, such as the presence of resin outside the cankers, were also higher in pruned plots. These results should be taken into account for future management of Monterrey Pine plantations.